2011
DOI: 10.1159/000330108
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Phage Display and Computational Algorithm by Mapping a Conformational Epitope of Bla g 2

Abstract: Background: Bla g 2, one of the major cockroach allergens, induces a strong IgE response against conformational epitopes, and on reexposure, sensitized individuals often display symptoms of allergic rhinitis and asthma. The aim of the current study was to perform a test of the efficacy of a modified phage display screening, characterization of selected phages and an automated algorithm, EpiSearch, in locating an important conformational epitope. Methods: The monoclonal antibody 7C11, which partially inhibits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…For instance while mapping for the major cockroach allergens Bla g 2 epitope, we sequenced 40 clones and obtained 32 clean sequences. Twenty-four out of 32 were SMMKADFDEEPR, and other 8 were SMMKADFEEEPR [3] ( see Note 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance while mapping for the major cockroach allergens Bla g 2 epitope, we sequenced 40 clones and obtained 32 clean sequences. Twenty-four out of 32 were SMMKADFDEEPR, and other 8 were SMMKADFEEEPR [3] ( see Note 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…EpiSeach (http://curie.utmb.edu/episearch.html) has been recently modified, and we successfully used it in combination with crystal structure analysis [2, 3]. …”
mentioning
confidence: 99%
“…Therefore, the phage display strategy is ideally suited for determination of individual polyclonal epitope recognition patterns. Phage display technology has been used to identify conformational epitopes in Ara h 1 and other allergens [42,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the pivotal role established for IgE in allergic reactions, little is known about the interaction between allergens and antibodies, mainly due to the low concentration of this class of immunoglobulin in the sera of patients and to the fact that IgE-producing B cells have been poorly characterized [reviewed by (Gadermaier et al, 2014)]. Most of the data related to this aspect are derived from in vitro assays using mouse monoclonal antibodies and/or recombinant chimeric human IgE derived from mouse antibodies (Tai et al, 2013;Tiwari et al, 2012). In this respect, it has been demonstrated that human allergen-specific IgE may interact in a different way from mouse antibodies (Aalberse and Crameri, 2011); therefore, these strategies may not be able to fully elucidate the overall spectrum of antibody recognition.…”
Section: Introductionmentioning
confidence: 99%